1991
DOI: 10.1007/bf00006420
|View full text |Cite
|
Sign up to set email alerts
|

Limited versus unlimited membership in microbial communities: evaluation and experimental tests of some paradigms

Abstract: Recent developments in community ecology have allowed for the synthesis of community models based

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Dispersal of organisms can play a significant role in determining large-scale patch dynamics (Brown et al 2011), and a model by Stevenson (1997) indicated this may be true for stream periphyton. However, empirical studies suggest that microalgal taxa have high dispersal ability (Finlay et al 2002), and often, there are many taxa in the species pool tolerant to a range of environmental conditions (McCormick and Cairns 1991, Vinebrooke 1996, DeNicola et al 2018). For such organisms, local environmental filtering appears to be the major determinant of their spatiotemporal distribution in streams (Padial et al 2014).…”
Section: Applications and Limitations Of The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersal of organisms can play a significant role in determining large-scale patch dynamics (Brown et al 2011), and a model by Stevenson (1997) indicated this may be true for stream periphyton. However, empirical studies suggest that microalgal taxa have high dispersal ability (Finlay et al 2002), and often, there are many taxa in the species pool tolerant to a range of environmental conditions (McCormick and Cairns 1991, Vinebrooke 1996, DeNicola et al 2018). For such organisms, local environmental filtering appears to be the major determinant of their spatiotemporal distribution in streams (Padial et al 2014).…”
Section: Applications and Limitations Of The Modelmentioning
confidence: 99%
“…However, empirical studies suggest that microalgal taxa have high dispersal ability (Finlay et al. 2002), and often, there are many taxa in the species pool tolerant to a range of environmental conditions (McCormick and Cairns 1991, Vinebrooke 1996, DeNicola et al. 2018).…”
Section: Applications and Limitations Of The Modelmentioning
confidence: 99%